NF-κB mediates inhibition of mesenchymal cell differentiation through a posttranscriptional gene silencing mechanism - Sitcheran, Raquel (Cold Spring Harbor Laboratory Press, 2003)
Cytokines, such as tumor necrosis factor-α (TNFα), potently inhibit the differentiation of mesenchymal cells and down-regulate the expression of Sox9 and MyoD, transcription factors required for chondrocyte and myocyte development. Previously, we demonstrated that NF-κB controls TNFα-mediated suppression of myogenesis through a mechanism involving MyoD mRNA down-regulation. Here, we show that NF-κB also suppresses chondrogenesis and destabilizes Sox9 mRNA levels. Multiple copies of an mRNA cis-regulatory motif (5′-ACUACAG-3′) are necessary and sufficient for NF-κB-mediated Sox9 and MyoD down-regulation. Thus, in response to cytokine signaling, NF-κB modulates the differentiation of mesenchymal-derived cell lineages via RNA sequence-dependent, posttranscriptional down-regulation of key developmental regulators.